Acute and Chronic Toxicity of Indoxacarb in Two Populations of Plutella xylostella (Lepidoptera: Plutellidae) - Lemes, Amanda A F [UNESP]; Sipriano-Nascimento, Thamiris P. [UNESP]; Vieira, Natalia F. [UNESP]; Cardoso, Camila P. [UNESP]; Vacari, Alessandra M.; De Bortoli, Sergio A. [UNESP] (Oxford University Press (OUP), 2021)
The diamondback moth, Plutella xylostella (Linnaeus, 1758), is one of the main pests of brassicas, and various insecticides, such as indoxacarb, are used to control it. However, frequent insecticide applications favor the selection of resistant individuals. Thus, the residual and sublethal effects of indoxacarb in two populations of P. xylostella, one collected in the field (FP) and one from the laboratory (LP), were evaluated and compared. The objective of this research was to investigate the toxicity of indoxacarb at residual and sublethal levels in a field population of P. xylostella from Brazil and a population from the laboratory. Leaf-dip bioassays showed high toxicity, with LC50 values after 48 h of 3.7 and 6.9 mg/liter for the LP and FP, respectively. Sublethal effects were indicated by significant reduction in the survival of larvae, pupae, and offspring. There was an increase in foliar consumption and a decrease in adult survival in the LP, and a decrease in fecundity in the FP. For the LP and FP population, the mean values for R0, rm, and λ for the control treatment were significantly higher than for the treatment groups (CL15 and CL25). Exposure of larvae to sublethal indoxacarb concentrations significantly reduced larval and pupal survival. Larval and pupal survival decreased as the indoxacarb concentration increased. Fecundity was significantly lower for the FP at LC15 (96.2 eggs per female) and LC25 (69.2 eggs per female) concentrations compared with the other treatments.
Keywords: diamondback moth; insecticide resistance management; oxadiazine